Remote sensing estimation of suspended sediment concentrations in highly turbid inland river waters: An example from the lower Jinsha tributary, Yunnan, China. - Liew, S. C (International Center for Remote Sensing of Environment, 2016)
Proceedings 30th International Symposium on Remote Sensing of Environment: Information for Risk Management and Sustainable Development, November 10-14, 2003, Honolulu, Hawai'i